Uji Efektivitas Ekstrak Etanol Daun Jambu Air (Syzygium aqueum) Terhadap Penyembuhan Luka Sayat Pada Kelinci Putih (Oryctolagus cuniculus) - Fauziah , Fani Nur; Samodra, Galih; Rahmawati, Nur (Journal of Pharmaceutical and Sciences, 2025)
Cut wounds, physical damage to the skin often caused by sharp instruments, require alternative treatments. This study aims to evaluate the effectiveness and determine the optimal concentration of water apple leaf (Syzygium aqueum) ethanol extract in accelerating the healing of cut wounds. Rose apple leaves are known to be rich in bioactive compounds such as flavonoids, alkaloids, and tannins, which have the potential to be wound healing agents. Extraction was carried out using the remaceration method with 96% ethanol for three days, and the extract was then formulated into concentrations of 5%, 10%, and 20%. Effectiveness tests were carried out on incision wounds on the backs of rabbits. The results showed that the healing time was inversely proportional to the extract concentration. The treatment group with a concentration of 5% healed on the 13th day, the concentration of 10% on the 12th day, while the concentration of 20% showed the highest effectiveness among all extract groups, with healing on the 10th day. Statistical analysis using the One Way ANOVA test (p=0.000; p<0.05) showed a significant difference between treatment groups. The higher the concentration of rose apple leaf ethanol extract, the faster the healing process of the incision wound, but the effectiveness of the 20% extract was still lower than the positive control (Bionet Cream), which healed the wound faster (10 days vs. 10 days) through a different mechanism, so further research is needed to compare their effectiveness statistically.